(untitled) (Journal of Partial Differential Equations, 1994)
We study the Calm-Hilliard equation with nonlinear principal part &#8706u&#8706t + D[m(u)(kD^3u - DA(u))] = 0 The existence of classical solutions is established by means of the method based on Campanato spaces and the energy estimates. The corresponding uniqueness is also proved.